Strengthening social capital as a strategy for edutourism development of Kampoeng Soesoe Randuacir Salatiga municipality - Satiani, Lasti Nur; Hadiwijoyo, Suryo Sakti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Educational tourism development is not only related to strengthening human capital, physical capital, financial capital and natural capital, but also requires social capital as an integrated part of the five livelihood assets. This research aims to identify the dynamics of social capital in the development of KampoengSoesoe as educational tourism, and construct a strengthening strategy in the development of KampoengSoesoe based on the typology of social capital owned. The research used a qualitative approach with a case study method, with data collection techniques carried out through observation, interviews and documentation studies. While the data analysis technique in this study was prepared by adopting an interactive model of qualitative data analysis techniques, using Robert Putnam's Social Capital Theory.The results showed that the social capital of the Randuacir Hamlet community in the form of trust, networks and norms, with various existing dynamics, is the strongest element in the development of KampoengSoesoeedu-tourism. Social capital provides many positive benefits for the development of KampoengSoesoe, including being able to increase community capacity which has an impact on increasing community income, as a medium to facilitate access to information and assistance provided by the government and other partners. In addition, it is also an effective means to maintain and preserve local customs and wisdom integrated into educational tourism activities.